2005
DOI: 10.1177/1073274805012004s03
|View full text |Cite
|
Sign up to set email alerts
|

Readiness and Capacity of Librarians in Public Libraries to Implement a Breast Cancer Outreach and Screening Campaign in Medically Underserved Communities

Abstract: Community-based partnerships are an important means of addressing cancer health disparities in medically underserved communities. Public libraries may be ideal partners in this effort. To assess the readiness and capacity of a public library system to implement cancer recruitment and outreach campaigns, 58 librarians in the Queens Borough Public Library System in New York completed self-administered questionnaires before and after a training on breast health, cancer, and screening. Results indicate that they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Public libraries and librarians have been used as a source to reach underserved groups (Goytia, Rapkin, Weiss, Golub, Guzman, et al, 2005). Several intervention strategies have been implemented successfully in these settings.…”
Section: Personal Cancer Communication 21mentioning
confidence: 99%
“…Public libraries and librarians have been used as a source to reach underserved groups (Goytia, Rapkin, Weiss, Golub, Guzman, et al, 2005). Several intervention strategies have been implemented successfully in these settings.…”
Section: Personal Cancer Communication 21mentioning
confidence: 99%
“…As a tumors form in postgerminal mature B cells, MM is regulated by expression of various cytokines and signal transduction molecules [23]. Released cytokines, chemokines and growth factors from myeloma cells interact with the microenvironment, causing auto-crine and paracrine secretion of insulin-like growth factor 1, interleukin-6 (IL-6), fibroblast growth factor receptor 3 (FGFR3), vascular endothelial growth factor (VEGF), tumor necrosis factor-α (TNF-α) and transforming growth factor-ÎČ [24].…”
Section: Pathophysiology Of MMmentioning
confidence: 99%
“…Released cytokines, chemokines and growth factors from myeloma cells interact with the microenvironment, causing auto-crine and paracrine secretion of insulin-like growth factor 1, interleukin-6 (IL-6), fibroblast growth factor receptor 3 (FGFR3), vascular endothelial growth factor (VEGF), tumor necrosis factor-α (TNF-α) and transforming growth factor-ÎČ [24]. The bone marrow microenvironment comprises several cell types such as hematopoietic cells, stromal cells, fibroblasts, bone marrow stromal cells (BMSCs), osteoblasts, osteoclasts, endothelial cells and immune cells, as well as noncellular components that include extracellular matrix, cytokines, growth factors and chemokines [23]. The onset of MM is due to the accumulation of abnormal plasma cells in the bone marrow that adhere to extracellular matrix and BMSCs, which play a key role in the pathogenesis of MM [25].…”
Section: Pathophysiology Of MMmentioning
confidence: 99%
“…Studies have also considered the lack of impact that public libraries have. Goytia et al (2005) investigated public libraries' capacity to support cancer screening in underserved communities to reveal significant attitudinal barriers on the part of the library staff. Gibson, Kaplan, and Vardell (2017) found that "libraries were the least frequently selected source of information" for parents of individuals with Autism Spectrum Disorder.…”
Section: Introductionmentioning
confidence: 99%